Inventories of building-blocks for the protection of architectural monuments in towns (Bulletin KNOB, 1995)
After 1945 Dutch town centers have gone through a drastic process of renovation. which has seriously affected the historical structure and the old buildings. The protection of the coherent structure of foundation, building-plots, urban spaces and buildings has not come out well in this process of change. The possibilities of the current legal instruments have not been utilized adequately.The inventories underlying the lists of ancient monuments and historic buildings, protected views of towns and villages, zoning plans and counselling concerning building- and demolition permits are not suitable for practice. Usually the inventoried historical elements and structures are not integrated or used as a source of inspiration in new-construction projects.In 's-Hertogenbosch a method of inventorying has been developed which records the main historical structure of the houses and their mutual coherence. By combining the building-blocks the historical architectural structure of the entire town-centre is made visible. Drawings are made of the building-plots and houses of each building- block on a geodetical foundation to a scale of l: 100.A drawing of the underground situation, comprising cellars, foundations, watercourses and the like, provides an insight into the old way of dividing into building-plots and the possible archaeological factors which are important for construction- and layout permits. A drawing of the ground floor with beam structure of the first layer of beams gives an impression of the layout of the houses and their mutual relations.These data are useful for the assessment of restoration and renovation plans. A cross-section drawing of the building-block shows the construction and build-up of the separate houses and their mutual relations. These data are of major importance for the building-technological assessment of plans. By combining these three drawings three-dimensional drawings can be made of building masses and urban spaces.These drawings can serve as a basis for town planners and architects in the development of new-construction projects in town-centers. For the compilation of lists of ancient monuments and historic buildings, inventorying of building-blocks is a more reliable method, because apart from the customary evaluation of the exterior, the interior and the building constructions of the monuments can also be assessed.The inventory of building-blocks is not only useful from a practical point of view, but also from a scientific one: analyzing the urban structure and researching the origin and development of the historic town. In 's-Hertogenbosch an interdisciplinary research project has been set up, linking archaeological, building-historical and historical studies of sources.The drawings of building-blocks are used as a basis for this. This article only discusses the practical applications of the inventories of building-blocks. To illustrate this, four examples of the application of inventories of building-blocks in 's-Hertogenbosch have been added.